Conspiracy in Camelot : the complete history of the assassination of John Fitzgerald Kennedy - Kroth, Jerome A. (Algora Pub., 2003)
This complete and up-to-date synopsis of the assassination of JFK (the actors, witnesses and investigators) weighs the different theories and looks at the drama as both a detective story and a defining moment in American mass psychology.